Exploring EFL Students’ Vocabulary Acquisition Strategies through English Movies - Siti Annisa; Ventje Jany Kalukar; Aridah Aridah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explores the vocabulary acquisition strategies used by EFL (English as a Foreign Language) students through English movies. Grounded in Krashen’s Input Hypothesis and Mayer’s Cognitive Theory of Multimedia Learning, the research investigates how learners engage with movie content to enhance their vocabulary. Using a qualitative method, the study involved two sixth-semester English Department students at a public university in Indonesia. Data were collected through semi-structured interview sessions and analyzed using thematic analysis. Findings reveal that students employ several strategies, including using English subtitles, noticing and repeating unfamiliar words, choosing genre-specific content, applying new vocabulary in writing and speaking, and rewinding scenes for better comprehension. In total, five key strategies were identified. These approaches helped learners connect vocabulary with context, improve pronunciation, and promote long-term retention. The use of multimedia, particularly movies, created an engaging and low-anxiety environment that supported incidental learning and increased motivation. The study concludes that learner-driven strategies supported by multimedia input significantly contribute to vocabulary development and suggests that educators integrate movie-based activities in language learning environments to enhance students’ vocabulary acquisition, contextual understanding, and motivation.